Evaluation of the thickness of acetabular cartilage by ultrasound in developmental dysplasia of the hip - Hong, Kai; Wan, Jie; Zhao, Ying; Zhang, Chao (Frontiers in Pediatrics, 2024)
Introduction It has been reported that the cartilaginous roof of the acetabulum is thicker in infants with developmental dysplasia of the hip (DDH) than in those with healthy hips. However, there is limited research on the changes in the thickness of acetabular cartilage after follow-up or treatment of DDH. This study aims to report the thickness of acetabular cartilage before and after treatment of DDH. Materials and methods In this prospective study, infants with clinical suspicion of DDH were enrolled in the pediatric outpatient service in our hospital from January 2022 to August 2023. The thickness of acetabular cartilage was measured in the standard coronal plane. Borderline hips (Graf IIa type) were monitored with monthly ultrasound examination until they were classified as normal hips (Graf I type), while dysplastic hips (Graf IIb type or worse) were treated with the Pavlik harness until they were also classified as normal hips in the final ultrasound examination. Results A total of 592 children [median age, 96 days (interquartile range, 70–142 days); 197 boys] were enrolled in the study. The thickness of acetabular cartilage in dysplastic hips (4.3 ± 1.6 mm) was greater than that in normal hips (3.0 ± .39 mm, P < 0.001) and borderline hips (3.1 ± .57 mm, P < 0.001). In borderline hips, the thickness of acetabular cartilage decreased from 3.1 ± .57 mm in the initial evaluation to 2.9 ± .53 mm in the final follow-up scan (P = 0.01). In dysplastic hips, the thickness of acetabular cartilage decreased from 4.3 ± 1.6 mm in the initial evaluation to 3.5 ± .51 mm after treatment (P = 0.003). The thickness of acetabular cartilage in dysplastic hips after treatment remained greater than that in normal hips (P < 0.0001). Conclusion The thickness of acetabular cartilage decreased after follow-up or treatment of DDH. Further research is required to determine whether cartilage that remain thicker in dysplastic hips than that in normal hips after treatment should be considered an early indicator of residual acetabular dysplasia.